A hierarchical hybrid monolith: MoS42−-intercalated NiFe layered double hydroxide nanosheet arrays assembled on carbon foam for highly efficient heavy metal removal. Issue 20 (13th May 2019) - Wang, Yongchuang; Gu, Yue; Xie, Donghua; Qin, Wenxiu; Zhang, Haimin; Wang, Guozhong; Zhang, Yunxia; Zhao, Huijun
Abstract : A novel hierarchical hybrid monolith have been fabricated for highly efficient and selective heavy metal decontamination, accompanied by facile separation. Abstract : Increasing exposure to heavy metals has stimulated extensive research for designing adsorbents with collective features of high removal efficiency and strong binding affinity to target ions as well as simple and facile separation. Herein, NiFe-layered double hydroxide (LDH) nanosheets have been homogeneously immobilized on a carbon foam (CF) substrate, followed by subsequent intercalation of MoS4 2− ions into the interlayers, giving rise to a hierarchical porous hybrid monolith (abbreviated as NiFe–MoS4 2− -LDH/CF). By virtue of abundant binding sites, strong affinity and excellent pore accessibility, the developed NiFe–MoS4 2− -LDH/CF hybrid monolith is found to be highly effective for the sequestration of Hg 2+, Pb 2+, and Cu 2+, exhibiting ultrahigh sorption capacities of 462, 299, and 128 mg g −1, respectively, and outperforms most of the reported sorbents. Meanwhile, the uptake kinetics of these metal ions are extremely fast, as reflected by >99% removal rates within 5 min. More significantly, the developed adsorbent possesses superior selectivity for the target heavy metals with high distribution coefficients in the presence of various interfering ions. Remarkably, the resulting NiFe–MoS4 2− -LDH/CF hybrid monolith can be utilized as a flow-through filter unit and continuously treat larger volumes of simulated wastewater to below the permitted level for drinking water as compared to a NiFe–MoS4 2− -LDH powder under identical dynamic conditions, highlighting its feasibility for practical water purification.